In vitro transfection of bone marrow-derived dendritic cells with TATp-liposomes - Pappalardo JS (Dove Medical Press, 2014)
Juan Sebastián Pappalardo,1–3 Cecilia A Langellotti,2 Sebastián Di Giacomo,1 Valeria Olivera,1 Valeria Quattrocchi,2 Patricia I Zamorano,1,2 William C Hartner,3 Tatyana S Levchenko,3 Vladimir P Torchilin3 1Virology Institute, Center for Research in Veterinary and Agronomic Sciences, National Institute for Agricultural Technology (INTA), Hurlingham, BA, Argentina; 2National Council for Scientific and Technical Research (CONICET), Autonomous City of Buenos Aires, Argentina; 3Center for Pharmaceutical Biotechnology and Nanomedicine, Northeastern University, Boston, MA, USA Abstract: Dendritic cells (DC) are antigen-presenting cells uniquely capable of priming naïve T cells and cross-presenting antigens, and they determine the type of immune response elicited against an antigen. TAT peptide (TATp), is an amphipathic, arginine-rich, cationic peptide that promotes penetration and translocation of various molecules and nanoparticles into cells. TATp-liposomes (TATp-L) used for DC transfection were prepared using TATp derivatized with a lipid-terminated polymer capable of anchoring in the liposomal membrane. Here, we show that the addition of TATp to DNA-loaded liposomes increased the uptake of DNA in DC. DNA-loaded TATp-L increased the in vitro transfection efficiency in DC cultures as evidenced by a higher expression of the enhanced green fluorescent protein and bovine herpes virus type 1 glycoprotein D (gD). The de novo synthesized gD protein was immunologically stimulating when transfections were performed with TATp-L, as indicated by the secretion of interleukin 6. Keywords: dendritic cell transfection, green fluorescent protein, bovine herpes virus 1 glycoprotein D, liposomes, TAT peptide, interleukin 6